Effects of fuzzless cottonseed phenotype on cottonseed nutrient composition in near isogenic cotton (Gossypium hirsutum L.) mutant lines under well-watered and water stress conditions1 - Bellaloui, Nacer; Turley, Rickie B. (Frontiers in Plant Science, 2013)
There is no information available on the effect of fuzzless seed trait on cottonseed nutrient composition (minerals, N, S, protein, and oil) under drought stress. The objective of this research was to investigate the effect of the fuzzless seed trait on cottonseed nutrients using four sets of near-isogenic lines (NILs). Each set consists of two lines that share the same genetic background, but differ in seed fuzziness (fuzzy, F; fuzzless, N). The near isogenic lines will enable us to compare the effect of the trait without confounding the genotypic background effects. We hypothesized that since the fuzzless trait involved in fiber initiation development, and was reported to be involved in biochemical, molecular, and genetic processes, this trait may also alter cottonseed nutrient composition. Results showed that NIL sets accumulated different levels of minerals in seeds and leaves, and the fuzzless trait (NF) in most of the lines altered seed and leaf mineral accumulations when compared with fuzzy lines (FN) or the control line. For example, K, P, Mg, Cu, and Na concentrations in seeds were higher in MD N and STV N than in their equivalent MD F and STV F lines. Leaf concentrations of Ca, K, Mg, S, B, Cu, and Fe in MD N lines were higher than MD F line. Lower levels of nutrients in seeds and leaves were observed under water stress conditions, especially Ca, Mg, N, and B in seeds. Generally and with few exceptions, seed protein was higher in fuzzy lines that in fuzzless lines; however, seed oil was higher in fuzzless lines than in fuzzy lines. Our research demonstrated that fuzzless trait altered the composition and level of nutrients in seed and leaves in well watered and water stressed plants. Differences in protein and oil between fuzzy and fuzzless seeds may indicate alteration in nitrogen and carbon fixation and metabolism. The differential accumulation of seed nutrients in this germplasm could be used by cotton breeders to select for higher cottonseed quality.